Incorporating the applications of Building Information Modeling (BIM) technology in the sustainable retrofitting of heritage buildings : A systematic review - Alawag, Aawag Mohsen; Alaloul, Wesam Salah; Liew, Mohd Shahir; Al-Awag, Eman Ali N.; Baarimah, Abdullah O.; Omer, Mazen Mohamed Alkhdar (Institute of Electrical and Electronics Engineers Inc., 2023)
The sustainable retrofitting of heritage constructions presents a unique set of challenges that require a comprehensive approach to address the historical and cultural significance, as well as energy efficiency, functionality, and safety. Building Information Modeling (BIM) technology has emerged as a promising tool for addressing these challenges. Thus, the purpose of this paper is to highlight the literature on the applications of BIM technology in the sustainable retrofitting of heritage constructions, with a focus on the advantages and challenges of this approach. To achieve this study's aim, the relevant literature was extracted from the Scopus database. Therefore, 41 papers were extracted from Scopus using a keyword search approach. Throughout the year 2013 to April 2023, the keyword search criteria contained the phrases 'BIM' AND 'HERITAGE' 'Retrofitting' AND 'CONSTRUCTION' OR 'REPAIR.'. In addition, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was used, and 14 out of 41 papers were chosen for comprehensive evaluation. A thorough examination of the selected articles highlighted the influence of BIM technology in the Sustainable Retrofitting of Heritage Constructions. Overall, incorporating the applications of BIM technology in the sustainable retrofitting of heritage constructions can help ensure that the retrofitting process is efficient, effective, and environmentally responsible.